Evaluating the Impact of Multimodal AIGC Tools on the Efficiency of Short Video Production - Mingda, Gao; Wai Yie, Leong (INTI International University, 2025)
The rise of AI-generated content (AIGC) is transforming the creative industry, especially in video production. With the fast-paced demands of short videos, creators increasingly rely on AI tools. However, most are single-function, like ChatGPT for text and SUNO for music. Multimodal AIGC tools integrate text, image, audio, and video generation, streamlining workflows by automating tasks such as scriptwriting, design, music production, and editing. This study explores the effectiveness of a multimodal AIGC tool developed by ByteDance called Jimeng, examining its potential to simplify workflows, reduce costs, and foster innovation in short video creation.Using experimental methods to quantify the efficiency of short video production by multimodal AIGC tools. Based on the experiment, the multimodal AIGC tools have improved the efficiency of short video production by over 100%, revealing the ability of AIGC to reshape the short video ecosystem and enhance creative possibilities.